Detection of viruses of Bangladeshi and Japanese garlic and their elimination through root meristem culture - Haque, MS; Hattori, K (Progressive Agriculture, 2017)
A number of viruses cause considerable yield loss and quality deterioration in garlic. Root meristems of virus infected plants are known to be free from detectable viruses. This potentiality could be exploited to obtain virus free clones at a high frequency by culturing excised root meristems in vitro. We have developed efficient methods of direct and somatic embryo derived shoot regeneration from root meristems of garlic. The objectives of this work were to detect viruses infecting Bangladeshi and Japanese garlic clones and find an easy and efficient method of eliminating the viruses for the improvement of both yield and quality of garlic. At first, we confirmed the presence of detectable viruses in three Bangladeshi and one Japanese clones. The clones were infected with four different types of viruses: Garlic viruses (GarVs), Onion yellow dwarf virus (OYDV), Leek yellow stripe virus (LYSV), and Garlic common latent virus (GCLV). To eliminate those viruses, as per our previous method, root meristems were cultured on MS medium supplemented with 1.0 µM NAA and 10.0 µM BA. Shoot primordia developed from the cultured explants within 1 month. The regenerated individual shoot buds (2-5 mm) were separated from the mother explants and transferred to growth regulators free medium. RT-PCR confirmed that the viruses present in the mother garlic plants were absent in the shoots found after two-step culture. The regenerated shoots were rooted on growth regulator free medium and transferred to pots. Results indicated that the plants remained free from LYSV. Virus elimination through root meristem culture emerged as an efficient novel technique for the eradication of multiple viruses as confirmed by RT-PCR in this study. This technique has the potential for the production and supply of virus free propagules (plants/bulblets) for the yield and quality improvement of garlic. Progressive Agriculture 28 (2): 55-63, 2017